Hubungan di antara amalan pengurusan keselamatan dan tingkah laku keselamatan di salah satu tapak binaan di Kota Kinabalu - Rushamizan, Rustam (2017)
This purpose of this study is to aimed at reviewing safety management practices and safety behaviors at one of the construction site in Kota Kinabalu. A sample was taken randomly consisting of 127 workers from 192 employees as a whole. Survey data was obtained by using questionnaire for workers at the site. The positive correlation value also indicates a positive relationship between the variables. Test results founded significant to all relationships between safety management practices and safe behavior. Safety training has the highest significant relationship within safety behavior (r = 0.515, p <0.01), followed by management commitment (r = 0.435, p <0.01) and the last is rules and procedures (r = 0.239, p <0.01). On the other hand, for regression tests, the results of the analysis showed that the three studied in this study were only significant safety training on safety behavior (B = 0.339, t = 3.496, p <0.01). However, it still requires a broader and deeper study. These findings provide valuable guidance for researchers and practitioners in identifying which mechanisms can enhance safety at work.